Lithium Disilicate crowns elaborated in system CAD-CAM: an aesthetic alternative in anterior endodontically treated teeth - Guevara-Galdámez, Deysi Cristina; Pérez-Valiente, Valeria Cristina; Reyes-García, Rafael Antonio; Amaya-Azurdia, Jorge Kevin; Ardón-Rivas, Katia Gisela; Ruiz-Urbina, Ronald Wilfredo; Wahn-Sosa, Erick (Revista Minerva, 2022)
The importance of this case is to structure a patient with innovative techniques to minimize clinical work time, in the Facultad de Odontología de la Universidad de El Salvador (FOUES), developing new knowledge for the area of new graduates for new skills and protocols, proposing an innovative alternative with favorable results for patients. A patient presented, requesting an aesthetic treatment for his four upper incisors with root canal treatment. The rehabilitation of the teeth was proposed with the use of cast posts and of Lithium Disilicate Crowns with Cut-back technique with the CAD-CAM processing system. As a final result, an excellent aesthetic and adequate rehabiitation were obtained through the integrated approach and innovative by applying new techniques, protocols and materials;obtaining results in this way in shorter clinical work and excellent quality.